KINERJA APARATUR DESA DALAM PELAYANAN PAJAK BUMI DAN BANGUNAN (PBB) DI DESA GANTIMULYO KECAMATAN PEKALONGAN KABUPATEN LAMPUNG TIMUR - Herman Sismono (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2020)
Land and building tax as one of the components that supports the balance fund, which has an influence on the amount of the balance of funds that will be received by the tax producing regions. Therefore, the UN needs serious attention from local governments. More precisely in terms of handling, so that later they will be able to make a large contribution to Regional Original Income (PAD). The formulation of the problem of this research is how the performance of village officials in Land and Building Tax (PBB) services in Gantimulyo Village, Pekalongan District, East Lampung Regency. The research objective was to determine the performance of village officials in Land and Building Tax (PBB) services in Gantimulyo Village, Pekalongan District, East Lampung Regency. This research used data collection methods by observation, interviews and documentation study. The main informants in this study were the village head, village secretary, head of planning and development, tax collection officers, and taxpayers. The data analysis used is data reduction analysis, data presentation and conclusions. Based on research and data analysis, it can be concluded that (1) The responsiveness of the village apparatus has gone well, namely by conducting socialization to residents to provide knowledge about land and building taxes. . (2) Responsibility in managing land and building tax funds is the Village Head, Village Treasurer/ Head of Finance, then Pak RT. (3) Accountability carried out by the village apparatus, namely by collecting land and building taxes from the residents then the funds are sent to the central government, from the center down to the villages in the form of direct assistance.Keywords: Land and Building Tax (PBB) Service, Village Apparatus Performance